Keadilan Lingkungan dan Pembangunan Berkelanjutan: Perspektif Hukum Lingkungan Melalui Hak Asasi Manusia dan Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Mustain Nasoha; Farisha Aulia Al Karima; Ma’rifatul Yuhairiaini; Luthfiyyah Az-zahra; Dewi Wulansari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research aims to analyze the concept of environmental justice within the framework of sustainable development through a human rights-based environmental law approach and the development of Islamic Sociological Jurisprudence Theory. The main issue examined is how environmental law can achieve substantive justice amidst the complexity of environmental damage and social inequality, and how the integration of sharia values ​​and social reality can strengthen this paradigm. The research method used is normative juridical with conceptual, legislative, and sociological approaches, enriched by an analysis of Islamic sociological jurisprudence theory. The results show that the human rights approach to environmental law provides a strong normative foundation for guaranteeing the right to a good and healthy environment, but still tends to be formalistic. Therefore, a more contextual and responsive approach through Islamic Sociological Jurisprudence Theory is needed, which integrates the principles of maqāṣid al-syarī‘ah (the principle of the welfare of the people), benefit (maṣlaḥah), and social reality in the process of legal discovery (rechtsvinding). This approach emphasizes the importance of the active role of law enforcement in interpreting the law in a progressive, multidisciplinary, and substantive justice-oriented manner. This study concludes that environmental justice from a sustainable development perspective requires not only compliance with positive legal norms but also a transformation of the legal paradigm toward a humanistic, adaptive, and socially just approach. The integration of human rights and Islamic Sociological Jurisprudence Theory can strengthen an environmental legal system that is more inclusive, sustainable, and oriented toward the welfare of the people and environmental sustainability.